2009
DOI: 10.1109/tpwrd.2008.2005369
|View full text |Cite
|
Sign up to set email alerts
|

Corrosive Sulfur Induced Failures in Oil-Filled Electrical Power Transformers and Shunt Reactors

Abstract: The nature and causes of corrosive sulfur induced failures are examined in oil-filled transformers and shunt reactors. Copper sulfide, which is formed when the corrosive sulfur in a mineral oil reacts with the copper conductors, is likely to diffuse into the paper tapes insulating the conductors. Since copper sulfide is partially conducting, the dielectric losses of the contaminated oil-impregnated-paper tapes are markedly increased; paper tapes in close proximity to the copper conductors are found to attain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 4 publications
0
58
0
Order By: Relevance
“…Unfortunately, researchers have recently faced a new problem, namely, corrosive sulfur in insulating oil. Corrosive sulfur can form the semi-conductor substance copper sulfide, which will be deposited on the paper surface [5,6]. Insulating resistance and dielectric property of oil-paper insulation have decreased because of emergence of this substance.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, researchers have recently faced a new problem, namely, corrosive sulfur in insulating oil. Corrosive sulfur can form the semi-conductor substance copper sulfide, which will be deposited on the paper surface [5,6]. Insulating resistance and dielectric property of oil-paper insulation have decreased because of emergence of this substance.…”
Section: Introductionmentioning
confidence: 99%
“…In the previous two decades, the systematic studies carried out throughout the world on transformer oil and oil immersed equipments and their breakdown have had clearly and conclusively proved that sulphur present in transformer oil and its reaction with copper conductors leads to the formation of copper and cupric sulphide [1][2][3][4][5][6]. The semi conducting copper sulfide which is formed on the copper conductor of windings, starts migrating towards inner papers layers [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, previous studies have shown how certain organic compounds containing sulphur (e.g. dibenzyl disulphide, DBDS) [11] are able to chemically attack copper surfaces immersed in insulating mineral oil causing metal displacement, promoted by oxygen, together with the formation of corrosive by-products such as copper sulphides (Cu x S) [12][13][14][15]. Copper sulphides, being ionic compounds, can interfere with the insulation system (solid and liquid components) reducing its reliability; this can result in catastrophic failure of high voltage assets, power distribution disruption and, ultimately, reputational and financial losses [16][17][18].…”
Section: Introductionmentioning
confidence: 99%